Vasorelaxant effects and its mechanisms of the rhizome of Acorus gramineus on isolated rat thoracic aorta - Jueon Lee; Sujin Shin; Junkyu Park; Ho-Young Choi; Kyungjin Lee (Scientific Reports, 2025)
Abstract In conventional medicine, the rhizome of Acorus gramineus Solander (AGR) is used to treat cardiovascular and cerebrovascular diseases. Decoctions containing AGR exert vasorelaxant effects. Therefore, this research aimed to delve deeper into the vasorelaxant effects and underlying mechanisms of AGR and its constituents (α-asarone and β-asarone). We assessed the vasorelaxant effect of a 50% ethanol extract of AGR (AGRE) using aortic rings from Sprague–Dawley rats pre-constricted with phenylephrine (PE) and potassium chloride (KCl). The findings suggested that the mechanism of this effect was independent of endothelial cells and was associated with vascular smooth muscle cells (VSMC). Since vasodilatory mechanisms associated with VSMC are predominantly influenced by K+ and Ca2+ channels, we explored various channels, including calcium-activated K+, voltage-dependent (delayed rectifier) K+, ATP-sensitive K+, inwardly rectifying K+, receptor-operated Ca2+ (ROCC), and voltage-dependent Ca2+ channels (VDCC). Selective blockers were used to examine K+ channels, which inhibited vasorelaxant effect of AGRE. These findings suggest that AGRE-induced vasorelaxation is facilitated through K+ channels. In addition, the blockage of Ca2+ influx was observed in both groups treated with PE and KCl. Therefore, AGR appears to block Ca2+ influx through ROCC and VDCC. In conclusion, AGR demonstrates vasorelaxant effects by acting on VSMC.